PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP PENYAJIAN KEMBALI LAPORAN KEUANGAN - Vira Fortuna Widyaningrum; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
This  study  aims  to examine  the  effect  of corporate governance  characteristics  on the financial restatement.  Indicators used to measure corporate governance mechanisms in this study are the size of board, proportion of independent board, size of audit committee, audit   committee independence, audit committee’s financial expertise, managerial ownership ,and institutional. While financial restatement are measured using dummy variable which used “1” if the firm restate and “0” if the firm non-restate.  This study also tests several control variables namely firm size, leverage, profitability, and industry. Data  for  this  study  are  obtained  from  annual  report  of  companies  listed  on Indonesia Exchange Stock (BEI) in 2009-2013. The sampling method used to draw the sample is purposive sampling. Sample contains from 19 restate companies and 19 non- restate companies. A control group comprising between restating firms and non-restating firmsare  matched  by  firm  size  and  industry.  The  criteria  of  restatement  companies allowed from GAO’s definition of restatement and exclude restatement that was happened due to application of new PSAK, accounting method changes, merge and acquisition that accordance  with  PSAK,  and  stock  splits  or  reverse  stock.  The  hypothesis  testing  use logistic regression analysis.The results  show that the size of board and institutional  ownership  negatively affects the financial restatement..  While proportion  of independent  board, size of audit committee,    audit   committee    independence,    and   managerial    ownership    did   not significantly   affect   restatement.   Overall,   it  can  be  concluded   that  two   corporate governance characteristics affect with occurance of restatement.